Microtubule organization during successive microsporogenesis in Allium cepa and simultaneous cytokinesis in Nicotiana tabacum - Y. N. Zhang; D. M. Wei; Y. Y. Song; L. Chen; X. Y. Zhu; H. Q. Tian (Biologia Plantarum, 2011)
Microtubule cytoskeleton organization during microspore mother cell (MMC) meiosis in Allium cepa L. and microsporogenesis in Nicotiana tabacum L. was examined. The MMC microtubules (MTs) were short and well dispersed in the cytoplasm of both taxa. As the MMCs of both species entered metaphase of meiosis I, the MTs constructed a spindle that facilitated the chromosomes to orient in the meridian plane. At anaphase of meiosis I, the spindle MTs differentiated into two types: one MT type became short, pulled the chromosomes toward the two poles, and was designated as centromere MTs; the second type of MT connected the two poles, and was designated as pole MTs. In A. cepa, where successive cytokinesis was observed, pole MTs assumed a tubbish shape. Some new short MTs aggregated in the meridian plane and constricted to form a phragmoplast, which developed into a cell plate, divided the cytoplasm into two parts and produced a dyad. However, in tobacco, a phragmoplast was not generated in anaphase of meiosis I and II and cytokinesis did not occur. The spindle MTs depolymerized and reorganized the radial arrangement of MTs from the nucleate surface to the periplasm during anaphase. Following telophase of meiosis II, the cytoplasm produced centripetal furrows, which met in the center of the cell and divided it into four parts, serving as a form of cytokinesis. In this process, MTs appeared to bear no relationship to cytokinesis.